2019
DOI: 10.5530/pj.2019.11.161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibacterial Activity of Lemongrass Oil Against Oral Clinical Isolates – An In vitro Study

Abstract: Background: There are 1,200 oral species out of which 400 are potentially important and 20 organisms are periopathic. Periodontal flora plays the important role in initiation and progression of periodontal diseases. There are various conservative and surgical procedures to treat and prevent periodontal diseases. Local drug delivery agents reduce microbial burden, blocks collagenase activity and inhibits bone loss; out of which tetracycline is common in use. Unwanted side effects and resistance of microorganism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…Lemongrass essential oil showed antibacterial activity higher than the control group which might be attributed to its chemical composition (table 3). Ilango et al, 2019 9 , reported antibacterial activity of lemongrass essential oil against streptococcus mutans at minimum inhibitory concentration of 10 µl. The major component of lemongrass as reported in table 3 is Z-Citral which represents more than 50% of the components.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lemongrass essential oil showed antibacterial activity higher than the control group which might be attributed to its chemical composition (table 3). Ilango et al, 2019 9 , reported antibacterial activity of lemongrass essential oil against streptococcus mutans at minimum inhibitory concentration of 10 µl. The major component of lemongrass as reported in table 3 is Z-Citral which represents more than 50% of the components.…”
Section: Discussionmentioning
confidence: 99%
“…However, the bacterial spectrum that could be inhibited due to fluoride release is still limited 6 . Addition of various synthetic constituents to glass ionomer cements was proposed in an attempt to enhance its antibacterial activity as chloroxylenol 6 , chlorhexidine gluconate 7 , doxycycline hyclate 8 , tetracycline 9 , ciprofloxacin, metronidazole and minocycline 10 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations